2006
DOI: 10.1007/s00246-005-1021-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Perceived Health of Children with Congenital Heart Disease After Attending a Special Sports Camp

Abstract: Sports camps for children with cardiac anomalies have existed for many years. However, no formal evaluation of the benefits of attending such camps has been undertaken heretofore. We assessed potential changes in the self-perceived health of children with congenital heart disease who attended a special sports camp. Thirty-one children with cardiac anomalies attended a 3-day multisports camp. Sixteen children, all of whom were 10 years or older, literate, and Dutch- or French-speaking, completed the Child Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 21 publications
5
51
0
8
Order By: Relevance
“…We corroborated our previous findings [5], showing that self-perceived health measured at the end of the sports camp is better than that measured before the camp. The immediate post-camp scores were significantly higher in 7 of 9 CHQ-CF87 dimensions.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…We corroborated our previous findings [5], showing that self-perceived health measured at the end of the sports camp is better than that measured before the camp. The immediate post-camp scores were significantly higher in 7 of 9 CHQ-CF87 dimensions.…”
Section: Discussionsupporting
confidence: 94%
“…The results of the present study replicate and extended those of our previous study conducted in 2004, in which we assessed changes in the perceived health of children with congenital heart disease attending a special sports camp [5]. The present study had a larger sample, and, moreover, determined whether the perceived health improvement in the children persisted three months after the camp concluded.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In their systematic review, Moola et al (2013) identified 21 studies of specialised therapeutic camps for children with chronic illnesses. The authors reported that in general, TR experiences tended to have some positive effects on the children with disabilities, including reduced aggression (Barr et al, 2010), improved wellbeing, self-perception, and emotional outlook (Bongiovanni, Clark, Garnett, Wojcicki, & Heyman, 2010), improved social and communication skills (Cushner-Weinsteine et al, 2007), increased self-esteem (Devine & Dawson, 2010;Torok, Kokonyei, Karolyi, Ittzes, & Tomcsanyi, 2006), improved self-management skills (Hunter, Rosnov, Koontz, & Roberts, 2006), higher peer acceptance (Meltzer & Rourke, 2005), better general physical and mental health functioning (Moons et al, 2006), better coping skills (Nicholas, Williams, & MacLusky, 2009), higher self-competence (Pulgaron, Salamon, Patterson, & Barakat, 2010), better quality of life (Shepanski et al, 2005), and general life satisfaction (Wu, Prout, Roberts, Parikshak, & Amylon, 2011). A range of other studies on specialised camps have also identified positive impacts for children with disabilities, including greater self-competence (Dawson & Liddicoat, 2009;Hill & Sibthorp, 2006), independence (Dawson & Liddicoat, 2009), social competence and sense of belonging (Dawson & Liddicoat, 2009;Lopata et al, 2010), positive parent-child communication skills (Walker, Barry, & Bader, 2010), care giving appreciation (Dawson & Liddicoat, 2009), ADHD symptom reduction (Hantson et al, 2012), diminished autism symptoms (Lopata et al 2010), reduction in anxiety (Briery & Rabian, 1999), and general physical and emotional empowerment, well-being, and satisfaction (Nettina, Donnelly, & Florio, 2003).…”
Section: Concept Mapping Analysis Of Social Skills Camp Experience Fomentioning
confidence: 96%